Distance Learning: Current Issues and Challenges - Umar, Umar (Foreign Language Instruction Probe, 2023)
Education that is delivered virtually, with neither the teacher nor the pupils physically present, is referred to as "distance learning. Although the terms "Distance Learning" and "E-learning" are frequently used interchangeably, they refer to two different concepts. The main difference between e-learning and distance learning is location. With e-learning, students can be together in a classroom while going through their digital lessons and assessments. Distance learning, on the other hand, can be done online and from the student’s home. The contact between teachers and students will vary as a result of the diversity in settings. This study employs a descriptive qualitative research methodology that depicts the scenario as it relates to an indicator or the current status of the findings in the field. A qualitative research process is one that generates descriptive data from people or observed behaviors as written or spoken words. In this study, the methods for gathering data and information were interviewing, and documenting studies of the necessary data sources. We come to the conclusion that the following needs will be met by this method of DLS improvement: (1) Improving the mapping between academia and industry; (2) Assist in keeping the skilled workers in the sector; (3) Bringing remote sector workers into the industrial job market on an equal footing with those who live in cities and towns and (4) Assist in the nation's development of an educated and cultural society.